IMPLEMENTASI PROGRAM LIFE SKILLS DAN OPTIMUM AGING BAGI LANSIA DI ASRI SENIOR DAY CARE AND LIVING WIYUNG KOTA SURABAYA - Hestyan, Alvian Pramadani; Susilo, Heryanto (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Asri Senior Day Care and Living is an institution in the form of a foundation that provides a number of elderly care services in order to achieve optimum aging. Asri SDC and Living is intended to facilitate the elderly to avoid loneliness, be independent, prosperous, and meaningful. The purpose of this study was to identify, describe and analyze the implementation of life skills and optimum aging programs for the elderly at Asri Senior Day Care and Living. This research uses qualitative research. The data sources in this study are foundation administrators, assistants / nurses, elderly program participants and elderly families. Data collection techniques used observation, interviews and documentation. The results showed that the life skills program at Asri Senior Day Care and Living was implemented in the form of health check services, physical fitness, counseling, learning and brain games, skills training and spiritual refreshment. The life skills program at Asri Senior Day Care and Living is implemented by foundation administrators, assistants / nurses, workers, and volunteers. Each life skills program is carried out on a scheduled basis three days a week and incidentally on other days. For elderly people who experience challenges, they will get assistance in the form of more assistance from Asri Senior Day Care and Living. The condition of the elderly in physical, psychological, cognitive, social relations, and spiritual aspects is in optimal condition through the activities that have been provided.